SELECTION OF LEEK FOR THE MIDLAND OF RUSSIA AT CULTIVATION NO SEEDLING METHOD - A. F. Agafonov; М. V. Dubova (Овощи России, 2018)
Leek very ancient culture which was widely applied in cookery and as remedy still by ancient Egyptians, Greeks and Romans. Now the leek is widespread in countries of Western Europe and North Africa, in the USA, Canada, Australia. On chemical composition it is one of the most valuable onions representing in fact "the alive table of Mendeleyev". In such countries as Belgium, Holland and France it is one of the main vegetable cultures, and annual production it per capita makes from 4 to 10 kg. In Russia, unfortunately, it is still rare culture though falls into to the most valuable types of an onion on biochemical structure, productivity, resistance to wreckers and diseases. Widespread introduction of a leek in production restrains a number of factors among which lack of early ripening varieties with the increased resistance to extreme environmental conditions, and in this regard – difficulty of receiving high-quality seeds of leek in a midland of Russia to the north of Rostov-on-Don. Therefore, a vital necessity is on the basis of study under various conditions of cooperation a "genotype is an environment" and selection from world collection of sources of economic-valuable signs, creation of productive sorts and hybrids with good resistance to cold, possessing in the conditions of Moscow Suburbs, along with the high productivity and quality of products, by a high adaptivity to the different terms of height winter spending. Results of long-term researches of laboratory of selection of onions cultures (VNIISSOK) on studying, assessment and selection of exemplars of grades of leek from the VIR world collection are presented in article, receiving hybrid combinations and lines, development of methods of selection and creation on this basis of grades and hybrids of leek for not seedling culture in a midland of Russia, possessing high rates of vegetable and seed efficiency, quality of production and winter hardiness.